Bifurcation analysis of laminar isothermal planar opposed-jet flow. (25th November 2016) - Liu, Shuang; Wang, Bofu; Wan, Zhenhua; Ma, Dongjun; Sun, Dejun
Highlights: Rich bifurcation phenomena of planar opposed-jet flow revealed by stability analysis. New stable and unstable solutions are identified. Bifurcation processes are sensitive to small symmetry-breaking imperfection. Model equations are constructed to present a simplified view of opposed-jet dynamics. Abstract: For a fixed geometric configuration, hydrodynamic instabilities and bifurcation processes of laminar isothermal planar opposed-jet flows with symmetric and slightly asymmetric inlet boundary conditions are investigated numerically using a high-resolution approach based on spectral element method. In current configuration, when inlet boundary conditions are symmetric, in the range of the Reynolds number considered ( Re ≤ 200), multiple new symmetry-breaking bifurcations are observed and four new flow patterns are identified. Their hydrodynamic characteristics are analyzed, in particular their symmetries. In addition, the case that inlet boundary conditions are slightly asymmetric is investigated. It is found that bifurcation processes are extremely sensitive to this small symmetry-breaking imperfection and much different from those in the symmetric case. Furthermore, model equations are constructed by symmetry consideration to explain the numerical results based on hydrodynamic equations.